2016
DOI: 10.1016/j.scriptamat.2016.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Sample size effects on strength and deformation mechanism of Sc75Fe25 nanoglass and metallic glass

Abstract: The mechanical properties and deformation mechanism of Sc 75 Fe 25 nanoglass and Sc 75 Fe 25 metallic glass pillars with diameter from 2 micrometers to 95 nanometers were investigated by means of ex-situ and in-situ compression tests. The results showed that the yield strength and deformation mechanism in the metallic glass were size-dependent while these in the nanoglass were not. It is suggested that the reduced shear band nucleation sites in metallic glass with decreasing sample size results in the increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 34 publications
5
35
0
Order By: Relevance
“…These length scales have important implications for size effects in plasticity. Extrinsic size effects common in monolithic metallic glasses [23,24,25] have been shown to be absent in nanoglasses albeit only over a narrow size range [26] and attributed to distributed plasticity promoted by the heterogeneities in the underlying amorphous structure. However, these heterogeneities are simultaneously responsible for an intrinsic size effect akin to the scaling behavior that derives from the role of microstructural length scales on plasticity in crystalline solids.…”
Section: Introductionmentioning
confidence: 99%
“…These length scales have important implications for size effects in plasticity. Extrinsic size effects common in monolithic metallic glasses [23,24,25] have been shown to be absent in nanoglasses albeit only over a narrow size range [26] and attributed to distributed plasticity promoted by the heterogeneities in the underlying amorphous structure. However, these heterogeneities are simultaneously responsible for an intrinsic size effect akin to the scaling behavior that derives from the role of microstructural length scales on plasticity in crystalline solids.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, it has been found that a Fe 90 Sc 10 nanoglass is ferromagnetic at 300 K, whereas the corresponding melt-quenched glass is paramagnetic, and only exhibits ferromagnetic order at a temperature below 200 K [5]. Moreover, nanoglasses have been reported to be more ductile, more biocompatible, and catalytically more active compared to the corresponding melt-quenched glasses [6][7][8][9][10][11][12][13][14]. Hence, by modifying the microstructure of nanoglasses using controlling the size of the amorphous grains (i.e.…”
mentioning
confidence: 99%
“…Moreover, a systematic study of nanosized and microsized Sc 75 Fe 25 HG and NG pillars by means of compression tests showed that both, yield strength and deformation mode, are size-dependent in HG pillars. These properties, however, are size-independent in the NG pillars (Wang et al, 2016b), which was attributed to the microstructural features present in the NG. Indeed, molecular dynamic (MD) simulations revealed that glass-glass interfaces in NGs act as nucleation sites for shear transformation zones (STZs) and prevent strain localization, which leads to the more homogeneous deformation of NGs as compared with HGs (Şopu et al, 2011;Adibi et al, 2013;Albe et al, 2013;Adibi et al, 2014;Şopu and Albe, 2015;Adjaoud and Albe, 2019;Cheng and Trelewicz, 2019b).…”
Section: Introductionmentioning
confidence: 99%